Cardiorespiratory Responses to Glittre ADL Test in Bronchiectasis: A Cross-Sectional Study - Ravoori Hena; Gopala Krishna Alaparthi; K. Shyam Krishnan; R. Anand; Vishak Acharya; Pretham Acharya (Canadian Respiratory Journal)
Background. Bronchiectasis is a chronic respiratory condition characterised by chronic sputum production, fatigue, and dyspnoea. These symptoms will lead to reduced exercise capacity and a reduced ability to carry out activities of daily living. Glittre ADL test is a valid and reliable test which evaluates the activities of daily living. Aim. To investigate whether the Glittre ADL test can differentiate the functional capacity and cardiorespiratory responses of patients with bronchiectasis from those healthy individuals using the six-minute test as a functional performance standard. Methods. This study included 30 subjects: 15 bronchiectasis and 15 age- and gender-matched healthy subjects. The patients and healthy subjects were made to perform the Glittre ADL and six-minute test on two consecutive days. Parameters such as time taken, distance walked, HR, RR, SpO2, and dyspnoea were recorded before and after the tests. Results. The performance of bronchiectasis was worse than the healthy group on the Glittre ADL test (4.78 ± 1.33 min, 3.94 ± 0.82 min, p=0.04). Distance walked in the six-minute walk test by the bronchiectasis was 42 meters lesser than the healthy (400.33 ± 77.99, 442 ± 89.21, p=0.18). The Glittre ADL test was correlated with 6MWT when the total sample was analysed (r=−0.41,p=0.05). There was moderate positive correlation between heart rate variation, dyspnoea, respiratory rate, and peripheral saturation (SpO2) between the tests (Glittre heart rate versus six-minute walk test heart rate (r=0.55,p=0.001); Glittre (Borg) versus six-minute walk test (Borg) (r=0.72,p=0.00); Glittre respiratory rate versus six-minute walk test RR (r=0.62,p=0.00); Glittre SpO2 versus six-minute walk test SpO2 (r=0.40,p=0.02)). The bronchiectasis group had a statistically significant higher (p=0.08,p=0.46) increase in dyspnoea and RR than the controls in both the Glittre ADL test and six-minute walk test (p=0.009,p=0.03), with the similar HR variation in both the groups (p>0.05). There was statistical difference in peripheral oxygen saturation in bronchiectasis in the six-minute walk test (p=0.03). Conclusion. The Glittre ADL test induced similar cardiorespiratory responses when compared to the six-minute walk test. So, the Glittre ADL test can be used as an assessment tool besides the six-minute walk test for the more complete evaluation of functional capacity and activities of daily living.